Shoulder the sky : a novel - Perry, Anne. (New York : Ballantine Books, 2004)
A World War I Chaplain and his family explore the mystery of a dead war correspondent and a powerful, sinister figure called the Peacemaker.
Accelerated Reader AR
Keywords: World War, 1914-1918 -- Trench warfare -- Fiction; World War, 1914-1918 -- England -- Fiction; Journalists -- Fiction; Great Britain -- History -- George V, 1910-1936 -- Fiction; Historical fiction; War stories